Comparison and suitability of genotype by environment analysis methods for yield-related traits of pearl millet - Lubadde, G.; Ebiyau, J.; Akello, B.; Ugen, M.A. (Uganda Journal of Agricultural Sciences, 2016)
Pearl millet (Pennisetum glaucum (L.) R. Br.) is an important food security and income crop for households living in semi-arid zones in Uganda. However, the genotype by environment interaction, in addition to the several methods used for its assessment, complicates selection of varieties adapted to such semi-arid areas. The objective of this study, therefore, was to compare common methods used to assess stability and adaptability of improved genotypes. Seventy six genotypes were planted in four environments in an alpha experimental design with two replications. Results showed that genotype by environment interactions were significant at p<0.05 for grain yield, days to 50% flowering and 50% physiological maturity, percentage of productive tillers and panicle area. Results further showed inconsistency in ranking of genotypes between methods; although Cultivar Superiority, REML, Yield Stability Index and GGE biplot were consistently correlated and identified high yielding and stable genotypes.
Keywords: GGE biplot; Grain yield; Pearl millet; Stability analysis